2015
DOI: 10.3390/coatings5040830
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Durable Exterior Clear Coatings for Wood

Abstract: Abstract:The goal of a durable exterior clear coating has eluded generations of coatings technologists, despite long-standing desire amongst the public for such a coating. The journey towards this goal initially focused on modifications to coating formulation, but took a completely different direction when it was found that a UV-transparent silicone clear coating on wood modified with chromic acid met consumer expectations of coating durability. This finding sparked world-wide interest in wood pre-treatments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 61 publications
7
89
0
4
Order By: Relevance
“…The results of the conducted experiments (Figures 2-7, Table 4) confirmed that the development of durable transparent surface protection for wood exposed to external conditions is complicated, and that the field of research in this area is still open [66]. This fact was emphasized even more through the use of oak as the underlying wood species.…”
Section: Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…The results of the conducted experiments (Figures 2-7, Table 4) confirmed that the development of durable transparent surface protection for wood exposed to external conditions is complicated, and that the field of research in this area is still open [66]. This fact was emphasized even more through the use of oak as the underlying wood species.…”
Section: Resultssupporting
confidence: 48%
“…The remaining treatments were characterized by a significant colour change compared to untreated oak wood (Figure 2), which was associated with a certain darkening after their application (see Table 2), and subsequent leaching by water associated with more significant changes in colour parameters (L*, a* and b*). Based on the results, it can be concluded that the use of UV-stabilizers only increases the colour stability of underlying wood if their leaching in external conditions is further prevented by a high-quality coating film [66]. According to the experimental results, using only the hydrophobic layer does not provide protection for the wood for a long period of time.…”
Section: Resultsmentioning
confidence: 80%
“…Future work will involve construction and testing of this proposed low cost device. As well as application to automotive coatings, the combination of the low cost LF-OCT device and graph search segmentation could be used for industrial coatings on wood [2] and in aerospace applications, such as thermal barrier coatings for aerospace turbine blades [49]. It may also be used for the automatic measurement of pharmaceutical tablet coating thicknesses [50].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of this variety are the heavy industry clear top coats in modern car paint systems [1], the do-it-yourself varnishing of outdoor wooden objects [2], and the highly specialised varnish coatings for valuable works of art [3]. This paper is focused on the economically important industrial coating context [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were attached to separate aluminium stubs using nylon nail polish and coated with a 10 nm layer of gold to make them electrically conductive. A scanning electron microscope fitted with a high brightness lanthanum hexaboride electron source (Cambridge Stereoscan 360, Leica Microsystems, Wetzlar, Germany) or a variable pressure scanning electron microscope (S-2600N, Hitachi Ltd., Tokyo, Japan) was used to obtain images of the tangential surfaces of samples after sanding or planing, and again after wetting and drying [17]. Loose material present at sanded or planed surfaces, both before and after wetting, was removed using transparent tape, and the tape was mounted on aluminium stubs and imaged using a scanning electron microscope, as above.…”
Section: Grain Raising Of Sanded Versus Planed Woodmentioning
confidence: 99%